1990
DOI: 10.1002/ejsp.2420200106
|View full text |Cite
|
Sign up to set email alerts
|

Type of academic training and causal attributions for social problems

Abstract: To provide evidence of the effects of academic training on causal attributions, university students in social science, commerce and engineering were compared at different points of their training in terms of their explanations of poverty and unemployment. Results of cross‐sectional analyses showed no field differences in causal attributions at the beginning of the first academic year but significant differences at the end of the year, with social science students blaming the system more than commerce or engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
0
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 32 publications
7
50
0
4
Order By: Relevance
“…When studying the different student groups we actually see interesting differences again. Students in economics (−0.094*) are less likely to blame "the system" while political science students after one semester are more likely to think that reforming "the economic structures" is the key to managing environmental problems (0.177 ¤ ) This is in line with results from previous research; social science students are more likely to suggest structural explanations while business/economics students are less likely to do so (Guimond et al 1989;Guimond and Palmer 1990).…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…When studying the different student groups we actually see interesting differences again. Students in economics (−0.094*) are less likely to blame "the system" while political science students after one semester are more likely to think that reforming "the economic structures" is the key to managing environmental problems (0.177 ¤ ) This is in line with results from previous research; social science students are more likely to suggest structural explanations while business/economics students are less likely to do so (Guimond et al 1989;Guimond and Palmer 1990).…”
Section: Resultssupporting
confidence: 85%
“…Research has shown that different types of education influence where people place the responsibility for societal problems. For example, Guimond, Begin and Palmer (1989), Guimond and Palmer (1990) have shown that social science students are more likely to give structural explanations to problems of unemployment and poverty, while business school students are more likely to attribute this to individual factors. In one of their studies they found that social science students are even more likely than poor/unemployed to give attributions to structural factors.…”
Section: Higher Education and Environmental Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Il s'agit simplement de ne pas comprendre une cohorte donnée d'étudiants universitaires en tant qu'entité monolithique, mais plutôt d'y discerner l'altérité des attitudes en fonction des filières académiques. Une longue série d'études, notamment Bernier (1978), Guimond (1992), Guimond, Bégin et Palmer (1989), Guimond et Palmer (1990, 1996, Franks, Falk et Hinton (1973), Hartnett et Centra (1977), confirme ces pré-dictions: d'importantes différences attitudinales sont décelées, dans le sens attendu, entre les étudiants en gestion et leurs condisciples sociologues. Mais il y a plus : outre les variations selon le domaine d'études, sont enregistrées des évolutions en fonction du niveau d'études.…”
Section: De L'influence Des éTudes Sur Les Attributions Causalesunclassified
“…Available data indicated that in the two sections of the general education course, 13% of the students were majoring in social science and 49% in business, whereas in the social psychology sections, 69% of the students were majoring in social science and 11% in business. These differing ratios might be relevant, because social science majors are more likely than business majors to blame situational factors for poverty and unemployment (e.g., Guimond & Palmer, 1990). However, covarying self-reported FAE understanding removed the course effects on two of three outcome measures, suggesting that social psychology students' greater understanding of FAE material was one contributor to those course effects.…”
Section: Discussionmentioning
confidence: 99%